Analytical and Clinical Evaluation of Two RT-qPCR SARS-CoV-2 Diagnostic Tests with Emergency Use Authorization in Ecuador - Freire-Paspuel, Byron (Am J Trop Med Hyg, 2021)
Dozens of RT-qPCR kits are available in the market for SARS-CoV-2 diagnosis, some of them with Emergency Use Authorization (EUA) by the Food and Drug Administration (FDA) or at least by a responsible agency of their country of origin, but many of them lack proper evaluation studies because of COVID-19 pandemic emergency. We evaluated the clinical performance of two commercially available kits in South America, the 2019-nCoV kit (Da An Gene, Guangzhou, China) and GenomeCoV19 kit (ABM, Richmond, Canada), for RT-qPCR SARS-CoV-2 diagnosis using the FDA EUA 2019-nCoV CDC kit (IDT, Coralville, IA) as gold standard. We found striking differences among clinical performance and analytical sensitivity in both kits; whereas the 2019-nCoV kit (Da An Gene) has a limit of detection of 2,000 copies/mL and 100% of sensitivity, the GenomeCoV19 kit (ABM) has a poor sensitivity of 75% and a limit of detection estimated to be over 8.000 copies/mL. The GenomeCoV19 kit (ABM) lacks clinical use authorization in Canada; however, the 2019-nCoV kit (Da An Gene) is authorized by the Chinese CDC. Our results support that only SARS-CoV-2 diagnosis kits with clinical use authorization from their country of origin should be exported to developing countries lacking proper evaluation agencies to avoid a deep impact of the COVID-19 pandemic due to unreliable diagnosis.